HAK MENDAHULUI TAGIHAN UTANG PAJAK UNTUK WAJIB PAJAK YANG DINYATAKAN PAILIT - PAULUS HERDIANTO MANURUNG (PREMISE LAW JURNAL, 2015)
A right to proceed the collection of tax debt is when a tax payer/tax guarantor has some personal debts (civil), but at the same time, he also has some debts to the country (fiskus). If his assets are not sufficient to pay all his debts, the country has the rights to proceed the tax debts. Of course, in carrying out the rights to proceed towards the assets of the bankrupted-tax payers, they will face other creditors who have the same interest. Therefore, it is important to be analyzed how the decision of rights to proceed to pay the tax debts to fiskus to the tax payers stated bankrupted, how the procedures to collect tax debts to the tax payers stated bankrupted, how the obstacles in the rights to proceed the tax debts to fiskus to the tax payers stated bankrupted. Keywords: Proceeding Right, Tax Debts, Bankruptcy